2014
DOI: 10.21608/jpp.2014.53723
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N-Forms and Bio-Stimulants on Productivity of Cucumber: 2- Flowering Characters, Yield and Its Components.

Abstract: To investigate the effect of nitrogen fertilization forms (ammonium sulphate and calcium nitrate) and some bio-stimulants (humic acid, fulvic acid, EM and yeast extract) under high temperature on flowering characters, yield and its components of cucumber (Cucumis sativus L.) cv. Prince, two field experiments were carried out in a private farm at El-Mahalla El-Kubra-Gharbia governorate during the two successive summer seasons of 2011 and 2012 Results showed that the (50%NH4 + 50%NO3) treatment of N-forms increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 6 publications
2
8
0
Order By: Relevance
“…Additionally, yeast extract contains vitamins, especially B-complex, enzymes, and phytohormones, such as auxins and cytokines [45,46]. The improvement of some vegetable crop attributes with the application of yeast extract was reported by previous studies [47][48][49][50] on the flowering characteristics of cucumber, as well as on melon growth [51].…”
Section: Effect Of Biostimulant Application On Growth Parameters Of Snap Beanmentioning
confidence: 99%
“…Additionally, yeast extract contains vitamins, especially B-complex, enzymes, and phytohormones, such as auxins and cytokines [45,46]. The improvement of some vegetable crop attributes with the application of yeast extract was reported by previous studies [47][48][49][50] on the flowering characteristics of cucumber, as well as on melon growth [51].…”
Section: Effect Of Biostimulant Application On Growth Parameters Of Snap Beanmentioning
confidence: 99%
“…Furthermore, the advantages of spraying yeast preparation on flowering characters could be due to its contain of essential bioconstituents, i.e., carbohydrates, protein, hormones (GAs, IAA, Cytokinins), minerals content and vitamins particulary B-complex vitamins which affected on physiological and biochemical processes in plants such as ion uptake, cell division and elongation, hormonal and enzymatic activities and this reflected on induces the growth as well as flowering (Barnett et al,1990 andVieira et al ., 2016).In addition, Hamail et al (2014) and Shehata et al (2016) reported that yeast treatments play a beneficial role in improving the formation of flowers in cucumber plants due to its effect on carbohydrates accumulation.…”
Section: B Effect Of Foliar Spray With Yeast Extract and Potassium Smentioning
confidence: 99%
“…Moreover, this effect may be attributed to its own content of various nutrients, high percentage of proteins, vitamins especially B-complex and levels of endogenous hormones, i.e., IAA and cytokinins (Barnett et al, 1990 andVieira et al, 2016) . In addition, Hamail et al (2014) on cucumber concluded that the advantages effect of yeast extract on increased yield could be attributed to the increment of leaf area and its influence on photosynthesis, accumulate more carbohydrates hence enhancement femaleness, as well as formed fruits. These results were consistent with the previous findings of Shehata et al (2012 and2016), , Nassef and El-Aref (2016) and Al-Madhagi (2019) on cucumber, as well as Morsy et al (2018) on melon, who found that foliar spray of yeast extract appear to have a positive effect of different cucurbit plants yield.…”
Section: B Effect Of Foliar Spray With Yeast Extract and Potassium Smentioning
confidence: 99%
See 1 more Smart Citation
“…Also, foliar of Moringa leaf extract at 20 percent recorded the highest production, minerals, and nutraceutical-related characteristics in stevia plants in comparison with other treatments (Hassan et al, 2021). Also, Hamail et al, (2014) study the impact of nitrogen fertilization forms and some bio-stimulants (humic acid, fulvic acid, EM and yeast extract) under high temperature on flowering characters, yield and its components of cucumber (Cucumis sativus L.) cv. Prince.…”
Section: Introductionmentioning
confidence: 98%